2002
DOI: 10.1021/ja026205k
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Optical Nonlinearity in a Self-Assembled Double-Strand Conjugated Porphyrin Polymer Ladder

Abstract: Addition of 4,4'-bipyridyl to a solution of a meso-meso butadiyne-linked conjugated zinc porphyrin polymer in chloroform results in self-assembly of a double-strand ladder complex. Excess ligand causes this duplex to dissociate into single strands. These binding processes were elucidated by near-IR and NMR titrations, as well as by gel permeation chromatography and small-angle neutron scattering. Ladder-making and -breaking are highly cooperative, with Hill coefficients of 3.0 and 3.7, respectively. Self-assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
103
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(107 citation statements)
references
References 17 publications
1
103
0
3
Order By: Relevance
“…Many studies have shown that the strength of the electronic coupling is maximized in ladder structures, in which the torsional angles between the segments are constrained to maintain the whole π-system in an essentially planar conformation. [25][26][27] Thus the conductance of biphenyl molecules, with a torsional twist angle φ between the two benzene units, is proportional to cos 2 φ. [13,14] Tape-like oligomers, in which there are more than one conjugated connections between each pair of monomer units, exhibit HOMO-LUMO gaps which decrease rapidly with increasing oligomer length, as illustrated by the acenes.…”
Section: Doi: 101002/adma201103109mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the strength of the electronic coupling is maximized in ladder structures, in which the torsional angles between the segments are constrained to maintain the whole π-system in an essentially planar conformation. [25][26][27] Thus the conductance of biphenyl molecules, with a torsional twist angle φ between the two benzene units, is proportional to cos 2 φ. [13,14] Tape-like oligomers, in which there are more than one conjugated connections between each pair of monomer units, exhibit HOMO-LUMO gaps which decrease rapidly with increasing oligomer length, as illustrated by the acenes.…”
Section: Doi: 101002/adma201103109mentioning
confidence: 99%
“…[43][44][45] The axial coordination chemistry of metalloporphyrins provides unique opportunities for controlling the three-dimensional conformations of porphyrin-based molecular wires via formation of double-stranded ladders, and other types of supramolecular assemblies. [27,[46][47][48] The rich photochemistry of porphyrins has been exploited to measure rates of photoinduced charge-transfer through porphyrin oligomers. [32,49,50] Photophysical and time-resolved microwave conductivity measurements have attested to the ability of these molecules to mediate charge transport over long distances.…”
Section: Doi: 101002/adma201103109mentioning
confidence: 99%
“…1, orthogonal orientation between porphyrins prevents the desired porphyrin-porphyrin π-conjugation. The conjugated porphyrin arrays, covalently linked by butadiynylene and ethynylene linkages (Piet et al, 1997;Anderson, 1994;Anderson, 1999;Thorne et al, 1999;Screen et al, 2002;Karotki et al, 2004;Drobizhev et al, 2004;Lin et al, 1994;Lin et al, 1995;Angiolilloet al, 2004), are assumed to be converted to cumulenic structures upon photoexcitation. This may make the absorption of the second photon favorable and enhance their nonlinear optical properties.…”
Section: Strong 2pa Of Conjugated Porphyrins By Self-coordinationmentioning
confidence: 99%
“…Aus diesem Grund wurde in den vergangenen Jahren eine Reihe großer Makrocyclen synthetisiert. [1][2][3] Lineare, konjugierte Porphyrinoligomere zeigen starke elektronische Fernkopplung [4][5][6] und ausgeprägtes nichtlineares optisches Verhalten, [7] was nur einige Beweggründe für die Synthese von cyclischen, konjugierten Porphyrinoligomeren sind. Zwar wurde bereits über viele cyclische Porphyrinoligomere berichtet, [8][9][10][11][12][13][14] allerdings fehlt den meisten von ihnen ein vollständiger p-Konjugationsweg entlang des gesamten Makrocyclus.…”
unclassified
“…K 0 kann näherungsweise als Konstante der Assoziation von 4-(Phenylethinyl)pyridin mit einem 5,10-Diethinylpor- [7,21] Die Synthese des cyclischen Octamers 1 stellt auch die allgemeine Auffassung infrage, dass Moleküle wie 3 "starre" oder "formbeständige" Stäbe sind. [23] Es ist bekannt, dass Polyine sich leicht in bogenförmige Konformationen biegen [24] und Porphyrine sich bereitwillig deformieren lassen.…”
unclassified